Development of a Pocket Book Based on Mind Mapping on Material Classification of Class VII Living Things - Nurul Fahriza; Ari Sunandar; Hanum Mukti Rahayu (Quagga: Jurnal Pendidikan dan Biologi, 2023)
The presence of learning media in teaching and learning activities has an important meaning. This study aims to develop a pocket book media based on mind mapping on class VII living things classification material. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection was carried out using a validated questionnaire for material experts, linguists, media experts, and student response questionnaires. The results showed that the developed mind mapping-based pocket book media scored 85% for the media aspect (very feasible), 85% for the language aspect (very feasible), and 94% for the material aspect (very feasible). While the results of student responses used 2 development trials, namely small-scale trials of 90.96% (Very Positive) and large-scale trials of 92.41% (Very Positive). It can be concluded that the pocketbook media developed is very feasible and gets a very positive response from students so it can be used in learning class VII living things classification material.